Bless the daughter raised by a voice in her head - Shire, Warsan, 1988- (London : Chatto & Windus for Penguin Random House UK, 2022)
"With her first full-length poetry collection, Warsan Shire introduces us to a young girl, who, in the absence of a nurturing guide, makes her own stumbling way towards womanhood. Drawing from her own life and the lives of loved ones, as well as pop culture and news headlines, Shire finds vivid, unique details in the experiences of refugees and immigrants, mothers and daughters, Black women, and teenage girls. In Shire's hands, lives spring into fullness. This is noisy life: full of music and weeping and surahs and sirens and birds. This is fragrant life: full of blood and perfume and shisha smoke and jasmine and incense. This is polychrome life: full of henna and moonlight and lipstick and turmeric and kohl"--
[Part 1]. What doesn't kill you -- [Part 2]. This is not a love song -- [Part 3]. Are you there, God? -- [Part 4]. Testament.
Keywords: Girls -- Poetry; Women -- Poetry; Somali poetry -- 21st century; English poetry -- 21st century; Refugees -- 21st century. -- Poetry